Epidemiology of surgical site infections post-cesarean section in Africa: a comprehensive systematic review and meta-analysis - Mohamed Baklola; Mohamed Terra; Mohamed Gamal Elsehrawy; Hatoun Alali; Sereen Saleem Aljohani; Aseel Ali Alomireeni; Razan Mubarak Alqahtani; Norah Majed Albalawi; Kawthar Abdulaziz Jafail; Alaa Jaffar Mohammed; Naji Al-Bawah; Mayas Hafez; et al. (BMC Pregnancy and Childbirth)
Abstract Background Surgical site infections (SSIs) are among the most common postoperative complications following cesarean section, particularly in Africa. These infections pose maternal health risks, including prolonged hospitalization, increased healthcare costs, and mortality. This systematic review and meta-analysis aimed to evaluate the epidemiology, pooled prevalence, and risk factors for SSIs after cesarean section in Africa. Methods A systematic search of PubMed/MEDLINE, Scopus, and Web of Science databases was conducted to identify studies published between January 2000 and December 2023. The review followed PRISMA 2020 guidelines, and 41 studies spanning 18 African countries met the inclusion criteria. Data on SSI prevalence and risk factors were extracted, and the quality of studies was assessed using the Newcastle–Ottawa Scale. A random-effects model was used to estimate pooled prevalence, with subgroup analysis, sensitivity analyses, and meta-regression exploring variations across study characteristics. Publication bias was assessed using funnel plots. Results The pooled prevalence of SSIs after cesarean section was 11% (95% CI: 9–12.9%) with substantial heterogeneity (I2 = 97%, < 0.001). Regional variations were observed, with the highest prevalence in Tanzania (34.1%) and Uganda (15%), and the lowest in Tunisia (5%) and Egypt (5.3%). Temporal trends revealed a peak in prevalence (16%) during 2011–2015, declining to 9.8% by 2016–2020. Prolonged rupture of membranes (PROM) was the most frequently reported risk factor (OR: 4.45–13.9), followed by prolonged labor (> 24 h) (OR: 3.48–16.17) and chorioamnionitis (OR: 4.37–9.74). Potential publication bias indicated by asymmetrical funnel plots. Conclusion SSIs following cesarean section remain a burden in Africa, with wide regional variations and multiple preventable risk factors. The findings highlight the need for targeted interventions, including improved infection control practices, antenatal care, and timely management of obstetric complications.